Economic risks of climate change : an American prospectus - Houser, Trevor (Columbia University Press, 2015)
From the opening commentary by Michael Oppenheimer, Princeton University:This work points the way toward a new era in climate risk analysis. It not only provides a basis for rationale judgments by policy makers but at the same time opens a new avenue toward progressive improvement in our understanding of risk.